(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the historical-ethnographic roots and specific features of the Uzbek mahalla from the Bronze Age to the Arab invasion based on written sources and archaeological research. In Turonzamin, a collective institution called today’s mahalla has existed since ancient times, and although it is not called a mahalla, territorial units of the same form can be found. Starting with the most ancient city-type settlements in our region, the traditions of the formation, development and management of the mahalla as a socio-economic association in the stages of historical development are described. Also, information about the way of social life and its tasks in the first administrative territorial units of the mahalla type is given.